Influence of Prenatal Drug Exposure, Maternal Inflammation, and Parental Aging on the Development of Autism Spectrum Disorder - Sato, Atsushi; Kotajima-Murakami, Hiroko; Tanaka, Miho; Katoh, Yoshihisa; Ikeda, Kazutaka (Frontiers in Psychiatry, 2022)
Autism spectrum disorder (ASD) affects reciprocal social interaction and produces abnormal repetitive, restrictive behaviors and interests. The diverse causes of ASD are divided into genetic alterations and environmental risks. The prevalence of ASD has been rising for several decades, which might be related to environmental risks as it is difficult to consider that the prevalence of genetic disorders related to ASD would increase suddenly. The latter includes (1) exposure to medications, such as valproic acid (VPA) and selective serotonin reuptake inhibitors (SSRIs), (2) maternal complications during pregnancy, including infection and hypertensive disorders of pregnancy, and (3) high parental age. Epidemiological studies have indicated a pathogenetic role of prenatal exposure to VPA and maternal inflammation in the development of ASD. VPA is considered to exert its deleterious effects on the fetal brain through several distinct mechanisms, such as alterations of -aminobutyric acid signaling, the inhibition of histone deacetylase, the disruption of folic acid metabolism, and the activation of mammalian target of rapamycin. Maternal inflammation that is caused by different stimuli converges on a higher load of proinflammatory cytokines in the fetal brain. Rodent models of maternal exposure to SSRIs generate ASD-like behavior in offspring, but clinical correlations with these preclinical findings are inconclusive. Hypertensive disorders of pregnancy and advanced parental age increase the risk of ASD in humans, but the mechanisms have been poorly investigated in animal models. Evidence of the mechanisms by which environmental factors are related to ASD is discussed, which may contribute to the development of preventive and therapeutic interventions for ASD.